Physiological maturity of seeds and colorimetry of fruits of Jatropha curcas L. - Dranski,João Alexandre Lopes (2010)
The objective was to relate the coloration of fruits of Jatropha curcas L during the maturation process with morphometric (fruits and seeds) and germinative characteristics (seeds). Fruits were collected at various maturation stages from mast trees located in Eldorado/MS, and six maturation stages were visually classified based on fruit's epicarp color. Epicarp digital colorimetry was used to characterize maturation stages in addition to morphometric variables of length and width of fruits and seeds, as well their water content. For determining the physiological potential it was used germination test, emergence velocity index and first count of germination. Results indicated that seeds of J. curcas should be harvested when fruit epicarp shows a reading equal or smaller than 82, 70 or 65 nm of red, green or blue scales from a digital color analyzer. Seeds of fruits with that colorimetry can be harvested in virtue of the maxim acumululation of dry mass, water content below 38,5% and higher physiological potential.